Relationship Between Short-Term Interest Rates and Excess Reserves : A Logistic Approach - Veyrune, Romain (IMF Working Papers; Working Paper ;, 2018)
This paper models the relationship between short-term rates and excess reserves in an interest rate corridor as a logistic function estimated for the Eurosystem. The estimate helps to identify conditions in which short-term rates become unanchored, that is, they move away from the policy rates and become more volatile within the interest rate corridor defined by the interest rates of the central bank's standing facilities. These conditions are attributed to coordination failures among counterparties at open market operations under fixed-rate and full-allotment procedures in the context of segmented markets. A model of the functioning of segmented markets describes how 'un-anchoring' takes place when counterparties pursue bidding strategies optimal from an individual perspective but sub-optimal from an aggregate perspective.